INNOVATIVE USE OF THE POTENTIAL OF CONTEMPORARY SENIORS - Urlińska, Magdalena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Attitude to old age varies depending on the cultural context - historical, like changing the public perception of the elderly and attitude to senior age. Since the 60s of the twentieth century in sociology is functioning the concept of ageism, describing the phenomenon of discrimination against older people because of their age. It manifests itself in a dismissive ratio deficits on offer for seniors or problems in the labor market. Social stigmatization of seniors has a direct impact on their physical and mental health. Sense of control over their own lives and to have a sense of whether the purpose is of great importance at the end of professional activity. Halting the process of marginalization of the elderly multi- faceted and complex solutions, parallel, integrated actions legal, financial, educational and psychological. Exploiting the potential which lies dormant in this social group gives positive changes. It becomes an element of counteracting the social stigma of old age, disenchant way of looking at modern senior. This scope for lifelong education, which is a bailout. It creates an action for the activity, gives the opportunity to make changes, positive transgression in the senior phase.Actions and initiatives designed to help them adapt to changing social reality and the market, they combine traditional teaching methods (lecture) with active methods (including mentoring). It is used in the process a wealth of experience as seniors. When preparing an offer of educational activities worth including senior-leadership initiatives. This senior-mentoring build on the expertise provides a wide range of knowledge about man and the surrounding reality, by which it is possible to transpose this knowledge from theory into practice. Flexibility in the method is adequate to the problems and needs of seniors, can properly select and modify rules educational activities, so that they are the optimal solution. Senior-mentoring can serve the liberation of spontaneous being and becoming elderly, activating its development opportunities and a nap in her creative potential. Comprehensive measures to help people in late adulthood in the learning process, to acquire new knowledge in the field of self-development and improved skills are an opportunity to make fuller use of the life and free timeEducation towards old age, conducted in the form of mentoring, is based on an individual plan of action, which in effect allows tame old age, it helps to find the meaning of life, develop a model of relationships with significant others, develop defenses and adaptation to difficult situations or emergencies, find in new roles. Senior-mentors, they could play an advisory role, on the one hand would indicate assisting the elderly, preventing their social exclusion and pathological aging, on the other hand, monitor and assist the process of education for old age.